Inclusive Higher Education in Kyrgyzstan for People with Physical and Intellectual Disabilities - Karabalaeva, Gulmira; Asipova, Nurbubu; Bayalieva, Aisulu; Niyazova, Janna; Karabalaev, Sultan (Journal of Intellectual Disability - Diagnosis and Treatment, 2024)
Considering the importance of education as a socio-cultural human right, the issue of implementation of inclusive higher education for persons with disabilities is relevant, determined by a set of legal, socio-pedagogical, technical, and financial problems. The study aims to investigate specific organizational and pedagogical factors facilitating the implementation of an inclusive higher education model in the Kyrgyz Republic. The study employed methods that included questionnaires of the subjects of the educational process and statistical analysis of the data obtained in the course of the questionnaire. Including the understanding of inclusion, the role of educational institutions, and effective methodologies for implementing inclusive practices in the educational process, key theoretical aspects were identified as a result of the analysis of modern theoretical concepts and methodological approaches to inclusive higher education. Furthermore, challenges such as the lack of adaptive infrastructure required for students with disabilities, as well as the insufficient preparation of teaching staff to work with the diverse needs of students, were highlighted. The study also covered the social and legal aspects of inclusive higher education in Kyrgyzstan. The legislative framework regulating the rights of students with disabilities was analyzed, and public support and awareness of inclusion in education were assessed. Based on the findings, specific recommendations and strategies were developed to improve inclusive higher education in Kyrgyzstan. These recommendations cover various areas, including educational programs, the training of educators, the creation of accessible infrastructure, and the development of social support programs. The practical relevance of this work lies in the possibility of implementing the recommendations and strategies proposed in this work to improve inclusive higher education in Kyrgyzstan, which contributes to a more accessible and equitable educational environment for all students.